2022
DOI: 10.1021/acs.iecr.2c02500
|View full text |Cite
|
Sign up to set email alerts
|

Dry Pressure Drop in a Two-Rotor Rotating Packed Bed

Abstract: Because of the centrifugal field in rotating packed beds (RPB), a process intensification of gas–liquid mass transfer takes place. While two-rotor RPBs offer a great potential to increase the separation performance, compared to one-rotor RPBs, there is a lack of fundamental understanding of hydrodynamics and mass transfer in two-rotor RPBs. To bridge that gap, systematic experimental approaches are needed to derive correlations for mass transfer and hydrodynamic behavior. The current article presents a detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…The operating conditions are set to rotational speeds of 180, 300, 600, and 900 rpm, gas load factor of 1.2 Pa , atmospheric pressure, and total reflux. The experimental procedures used are described in detail in Pyka et al 15 The geometry of the RPB A and properties of the packing are listed in Table 1 and are the same as reported in the publication by Qammar et al 11 The vapor bypassing the rotor through sealing can be determined during distillation for binary test systems by temperature measurement. Figure 3 shows the location of the temperature measurement for bypass determination.…”
Section: Influence Of Different Sealing Types On Separation Performan...mentioning
confidence: 99%
See 1 more Smart Citation
“…The operating conditions are set to rotational speeds of 180, 300, 600, and 900 rpm, gas load factor of 1.2 Pa , atmospheric pressure, and total reflux. The experimental procedures used are described in detail in Pyka et al 15 The geometry of the RPB A and properties of the packing are listed in Table 1 and are the same as reported in the publication by Qammar et al 11 The vapor bypassing the rotor through sealing can be determined during distillation for binary test systems by temperature measurement. Figure 3 shows the location of the temperature measurement for bypass determination.…”
Section: Influence Of Different Sealing Types On Separation Performan...mentioning
confidence: 99%
“…Recent studies focused on the actual design of the contributing parts of the RPB unit, such as the liquid distributor and the variation of the sealing at the eye of the rotor, which play a dominant role in the overall performance of the unit. 14,15 However, likewise to other technologies, the overall performance of a technical unit is determined not only by its main characteristics, i.e., the packing in RPBs. Also, other components like the sealings have a significant influence on the processes.…”
Section: Introductionmentioning
confidence: 99%
“…labyrinth sealing may lead to a vapor bypass, as demonstrated previously. 18 2.2. Chemicals and Analytics.…”
Section: Methodsmentioning
confidence: 99%
“…16,17 This setup allowed studying the influence of the reflux ratio on distillation in 1R-RPBs in order to operate the 1R-RPB in a continuous separation process. 16,17 Recently, Pyka et al 18 showed the importance of using sealings in distillation experiments in 1R-RPBs. It was demonstrated that it is essential to avoid vapor bypasses in order to achieve a high separation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Pyka et al introduced a novel liquid distributor for an RPB called a rotating baffle distributor (RBD). 31 Comparing the overall separation efficiency in an RPB, the authors showed that RBD is one theoretical stage superior to the conventional liquid distributor (full jet nozzles) and is also helpful in solving the liquid distribution problem in multirotor RPB.…”
Section: Change In the Separationmentioning
confidence: 99%